CONGENITAL STENOSIS OF THE EXTERNAL AUDITORY CANE WITH CHOLESTEATOMA IN CHILDREN (Zamonaviy dunyoda amaliy fanlar, 2025)
Congenital stenosis of the external auditory canal in children is a rare but clinically significant pathology, often combined with microtia and middle ear anomalies. One of the most serious complications of this anomaly is the development of cholesteatoma, leading to destruction of the temporal bone and persistent hearing loss. The aim of this study is to analyze modern surgical approaches to the treatment of children with this pathology, including an assessment of indications for surgery, diagnostic criteria and postoperative results.